Layer-by-layer coating of single cell Lactobacillus rhamnosus GG to increases viability under simulated gastrointestinal conditions. - Sbehat, Maram (Maram Mohammad Sbehat, 2020)
This study was conducted to evaluate the viability of Lactobacillus rhamnosus GG microencapsulated by layer-by-layer (LbL) technique with black seed protein (BSP) extracted from Nigella sativa defatted seeds cakes (NsDSC), as a coating material, with alginate, inulin or glucomannan, separately, and the final coating layers number was three. The viable cell counts of the plain and coated L. rhamnosus GG were determined under sequential simulated gastric fluid (SGF) for 120 min and simulated intestinal fluid (SIF) for 180 min. Additionally, the viability after exposure to 37, 45 and 55°C for 30 min was also determined. Generally, the survivability of coated L. rhamnosus GG showed significant (p<0.05) improvement (<4, 3 and 1.5 logs reduction) comparing to plain cells (~6.7 log cycle reduction) under sequential exposure to SGF and SIF. Moreover, the coated cells were superior over plain cells under treatment with high temperatures. The study has shown that, BSP and inulin have provided the best protection of L. rhamnosus GG against either in simulated GI conditions or under heating temperatures. In conclusion, the LbL technique showed a significant protection of probiotic cells, making it a promising method to maintain high viable count of probiotics through host’s GI.
Keywords: Layer-by-layer coating of single cell Lactobacillus rhamnosus GG to increases viability under simulated gastrointestinal conditions.